Genetic yield potential of rice (Oryza sativa) through water saving and high-yielding SRI technology - GHRITLAHRE, SURENDRA K; SARIAL, ASHOK KUMAR; RAM, MANGAT; ANEJA, DES RAJ; SINGH, RATTAN (The Indian Journal of Agricultural Sciences, 2012)
In this investigation 20 rice genotypes were evaluated for yield and other traits under SRI and conventional system to identify suitable cultivars for SRI. In general, genotypes flowered earlier but matured late in SRI than conventional method. A majority of the genotypes attained more biological yield and grain yield/plant in conventional over SRI method. However, four genotypes namely; IR 64 (24.31%) HKRH 1094 (15.21%), Pusa 1121 (12.54%), and HKR 46 (11.78%) yielded higher in SRI over conventional. IR 64 is a widely adapted cultivar grown over a number of countries including India, whereas HKR 46 has been released for and cultivated in Haryana state. Pusa Basmati 1121 was released for commercial cultivation in 2003 for Haryana state but it’s occupying about 60% of the total basmati area in northern India and contributed foreign exchange to the tune of INR  5000/crores annually (www.icar.org.in 2009). These genotypes identified superior for grain and biological yield could be tested over macro-environments of space and time and recommended for cultivation in SRI production system.